Unveiling Bowen’s disease on lower limb: a case report of long-term misdiagnosis as dermatitis - Djuanda, Stephanie D.; Prayogo, Danniel L.; Djuanda, Dani; Tanurahardja, Budiana; Winaya, Ketut K. (International Journal of Advances in Medicine, 2025)
Bowen’s disease (BD) is a pre-cancerous condition classified as in-situ cutaneous squamous cell carcinoma (CSCC) of the epidermis. Several studies have shown that the condition requires prompt diagnosis and treatment due to its progressive nature. Despite the urgency of treatment, misdiagnoses are common due to similarities to dermatitis or psoriasis. Therefore, this report presents the case of a 69-year-old man with a hyperpigmented erythematous plaque on the right lower leg, which was misdiagnosed as nummular dermatitis for over 10 years. The patient reported the long-term use of corticosteroids, but the lesion persisted. Physical examination showed a 35×40 mm irregular plaque with excoriation. A skin biopsy showed full-thickness epidermal atypia, confirming BD. The lesion was surgically removed with a 4 mm margin, and an O-Z flap was used for closure. After the treatment, no recurrence was observed at 6 months of follow-up. BD often mimics other dermatological conditions, leading to delayed diagnosis. This case underscores the importance of biopsy in chronic skin lesions, especially when treatments fail. Surgical excision remains the most reliable treatment, offering a high success rate and low recurrence. Non-surgical options, such as photodynamic therapy and topical agents, have lower efficacy. In this case, the surgical approach with a 4 mm safety margin ensured complete removal while minimizing recurrence risk. This report showed the significance of early and accurate diagnosis of BD to prevent progression to invasive CSCC. Surgical excision was the preferred treatment for BD, offering high cure rates and minimizing complications.